THU0133 Serum pentraxin-3 in the assessment of cardiovascular risk in patients with rheumatoid arthritis. (15th June 2017) - Targonska-Stepniak, B; Piotrowski, M; Zwolak, R; Majdan, M
Abstract : Background: Rheumatoid arthritis (RA) is associated with the increased cardiovascular (CV) morbidity and mortality due to accelerating, progressive atherosclerosis. The chronic, systemic inflammatory process is responsible for both joint damage and increased CV risk in RA patients. Pentraxin 3 (PTX3) is an inflammatory marker, a member of long pentraxin superfamily, supposed to be involved in inflammatory process as well as in atherosclerosis. Objectives: The goal of the study was to assess the role of PTX3 as an inflammatory marker in patients with RA and to evaluate the relationship between PTX3 and CV risk markers [carotid intima-media thickness (cIMT), QTc distance (dQTc), lipid profile]. Methods: The study group consisted of 72 consecutive RA patients, 60 (83, 3%) female and 12 male (16, 7%), with the mean (SD) age 53, 4 (10, 29) (range 21–71) and disease duration 16, 8 (10, 3) years (range 2–49). The activity of RA was estimated by clinical examination with the disease activity score in 28 joints (DAS28). Remission or low disease activity was observed in 35 (48, 6%) patients; moderate or high disease activity (DAS28 >3, 2) in 37 (51, 4%) patients. Disease modifying antirheumatic drugs (DMARDs) used in the treatment included: methotrexate 61 (84, 7%) patients, chlorochine or hydroxychlorochine 9 (12, 5%), leflunomide 4 (5, 6%), cyclosporine 1 (1, 4%) patient. The majority of patients 54 (75%) were treated with biological DMARDs, currently or in the past. Results: The mean (SD) PTX3 concentration in RA patients was 4, 57 (2, 83) ng/ml (range 1, 43- 16, 07). The mean (SD) cIMT value was 0, 86 (0, 2) mm (range 0, 43–1, 77). There were 19 (26, 4%) RA patients with advanced atherosclerosis (presence of atherosclerotic plaques). The positive, significant correlations were found between PTX3 concentration and other inflammatory markers: C-reactive protein (CRP) (R=0, 5), ESR (R=0, 46) and white blood cell count (WBC) (R=0, 41). PTX3 concentration was also correlated with clinical disease activity markers: DAS28 value (R=0, 41), as well as with tender joint count (TJC) (R=0, 01), swollen joint count (SJC) (R=0, 009), patient's global assessment of the disease activity (R=0, 02). The mean (SD) PTX3 concentration was significantly higher in patients with moderate/high RA activity in comparison with remission/low disease activity [5, 56 (3, 29) vs 3, 48 (1, 71) ng/ml, p=0, 001] and in patients anti-CCP positive compared with anti-CCP negative [4, 57 (2, 58) vs 3, 02 (0, 85) ng/ml, p=0, 04]. The mean (SD) PTX3 concentration was significantly higher in patients with definite atherosclerosis (cIMT >0, 9 mm) than in patients with subclinical or no atherosclerosis [5, 77 (3, 02) vs 3, 99 (2, 58) ng/ml, p=0, 04], as well as in patients with atherosclerotic plaques in comparison with no plaques (6, 18 (2, 83) vs 4, 02 (2, 64) ng/ml, p=0, 0006). There was a negative correlation between PTX3 and dQTc (R= -0, 33, p=0, 007). Conclusions: The results of the study suggest a twofold role of PTX3: 1. an inflammatory marker of the joint disease activity 2. a biomarker indicating intensity of atherosclerosis, estimated by greater cIMT value and the presence of atherosclerotic plaques. The negative correlation between PTX3 and dQTc suggests the increased risk of sudden cardiac death due to shortening of dQTc. Disclosure of Interest: None declared